Ascorbic acid microencapsulation by spray‐drying in native and acid‐modified starches from different botanical sources. Issue 7 (30th January 2013) - Palma‐Rodriguez, Heidi M.; Agama‐Acevedo, Edith; Gonzalez‐Soto, Rosalia A.; Vernon‐Carter, E. Jaime; Alvarez‐Ramirez, Jose; Bello‐Perez, Luis A.; Tester, Richard F.
Abstract Native starches (NS) of maize (M), potato (P), and rice (R) were subjected to mild acid treatment for producing modified starches (ModSs). NRS and all the ModS were used for microencapsulating ascorbic acid (AA) by spray‐drying. AA retention %, surface AA %, AA stability, particle size analysis, glass transition‐water activity behavior and morphology of the microcapsules were studied. NRS microcapsules resembled "popcorn" balls of starch granules bound together by protein bridging. ModS microcapsules morphology was characterized by individual starch granules with differing particle size distribution. NRS microcapsules exhibited the initial lowest AA retention % and lowest surface AA %, but also suffered the lowest AA degradation upon storage. Among the ModS microcapsules those made with ModMS showed significantly lower AA degradation during storage. AA stability was closely associated to surface AA %. Peaks in glass transition temperature (Tg) occurred for ModPS and ModMS microcapsules at water activity (aw) of ∼0.34, and for the ModRS microcapsules at aw of ∼0.42. The NRS microcapsules exhibited a monotonous decrease in Tg with increasing aw values. Based on these results storage stability conditions were set at aw = 0.328 ± 0.002 and 25°C, in order to minimize the structural changes of all the starch matrices with storage time.